2022
DOI: 10.3389/fimmu.2022.921293
|View full text |Cite
|
Sign up to set email alerts
|

Modified combination of anti-thymocyte globulin (ATG) and post-transplant cyclophosphamide (PTCy) as compared with standard ATG protocol in haploidentical peripheral blood stem cell transplantation for acute leukemia

Abstract: In haploidentical peripheral blood stem cell transplantation (haplo-PBSCT), the combination of anti-thymocyte globulin and post-transplant cyclophosphamide (ATG/PTCy) has a synergistic impact in preventing graft-versus-host disease (GvHD). However, little is known about the long-term consequences of the new combination approach. Our goal is to evaluate the efficacy of ATG/PTCy versus a standard ATG regimen by focusing at long-term outcomes in a more homogeneous group of patients. We retrospectively included 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
2
2
2
Order By: Relevance
“…Incidence of GVHD was 44.1% in ATG + PTCy arm and it was higher at 66.7% in PTCy alone arm. Our results of the PTCy+ATG arm are in keeping with data published by Barkhordar et al [24].…”
Section: Discussionsupporting
confidence: 93%
“…Incidence of GVHD was 44.1% in ATG + PTCy arm and it was higher at 66.7% in PTCy alone arm. Our results of the PTCy+ATG arm are in keeping with data published by Barkhordar et al [24].…”
Section: Discussionsupporting
confidence: 93%
“…However, recent investigations have showed that preemptive therapy with glucocorticoids for aGvHD did not increase the incidence of infection 23,24 . Meanwhile, many studies have reported that the high incidences of CMV reactivation and hemorrhagic cystitis (ranging from 31% to 70% and 27.8% to 36%, respectively) in the setting of PTCy‐based aGvHD prevention regimens 25–31 . In our study, preemptive therapy with methylprednisolone for aGvHD did not show a significant increase in infection‐related events, cumulative incidences of CMV reactivation, or grade 2 or higher hemorrhagic cystitis, as determined by the chi‐square test.…”
Section: Discussioncontrasting
confidence: 57%
“…23,24 Meanwhile, many studies have reported that the high incidences of CMV reactivation and hemorrhagic cystitis (ranging from 31% to 70% and 27.8% to 36%, respectively) in the setting of PTCy-based aGvHD prevention regimens. [25][26][27][28][29][30][31] In our study, preemptive therapy with methylprednisolone for aGvHD did not show a significant increase in infection-related events, cumulative incidences of CMV reactivation, or grade 2 or higher hemorrhagic cystitis, as determined by the chi-square test. These findings suggested that MAP-guided preemptive therapy for aGvHD with methylprednisolone is safe and feasible, complementing the existing routine prophylaxis for aGvHD while maintaining definite efficacy.…”
Section: Discussioncontrasting
confidence: 39%
“…Data provided by the Center for International Blood and Marrow Transplant Research (CIBMTR) in a large cohort study revealed that donor sex, donor pregnancy history, and recipient age were significantly associated with the onset of cGVHD ( 2 ), while donor parity was the sole variable that significantly influenced the risk of extensive cGVHD in our study. Regarding the augmented risk of cGVHD, the predictive effects of other factors such as aGVHD grades I-IV, males receiving grafts from allo-immunized females, and donors age have all been recognized significant in the multivariate analyses by previous studies ( 10 , 22 24 ).…”
Section: Discussionmentioning
confidence: 99%